The Venue Attributes on Customer Satisfaction of Balinese Dinner in Bali Case Study : Megibung Event at The One Legian Hotel - Firman Sinaga; Santi Palupi; Sabalius Uhai; Muhammad Ali (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The tourism industry plays a crucial role in contributing significantly to the economy, particularly through increased tourism activity, increased cash flow, and the potential for increased local income. This study aims to analyze the influence of venue attributes on customer satisfaction at a traditional Balinese dinner (megibung) at The One Legian Hotel. Method: This study was conducted over three months at the research location, One Legian Hotel, which conducted a two-part study. First, a descriptive research approach was used to determine respondents' perceptions of venue attributes. Second, a correlational research approach was used to analyze the influence of venue attributes on guest satisfaction during the Mengibung event. Results: The results showed that guests rated the service as very satisfactory, the decor very beautiful, the price very reasonable, the food very delicious, the ambiance very good, and the facilities very complete. Meanwhile, guests had a high overall satisfaction score of 3.62 (very satisfied). Of the six place attribute variables, there is a significant positive impact (p < 0.05) on satisfaction: price (X3) with 1 price indicator in relation to dinner quality, atmosphere (X5) with 1 place atmosphere indicator, and food (X4) with 2 indicators: appearance and color. Conclusion: High customer satisfaction leads to increased loyalty and repeat visits, ultimately contributing to the growth of the events industry and increased revenue for businesses and the surrounding community. Therefore, events like megibung not only provide a quality tourism experience but also improve the economic well-being of the community through job opportunities and increased income